Berbagai Teknik Penanganan Bruksisme - Erna Kurnikasari (Jurnal Material Kedokteran Gigi, 2013)
Bruxism is parafungsional activity includes clenching and grinding motion on day or night during sleep. Signs bruksisme most easily observed is the presence of attrition, fracture teeth and increase tooth sensitivity and degree of mobility. Bruksisme can also cause temporomandibular joint disorders, eksostosis and torus in the jaw bone, muscle hypertrophy mastication, periodontal tissue damage, as well as causing headaches, after the pain patients seeking help. Bruksisme etiology is multifactorial, with psychological factors such as stress, local factors such as premature contact, systemic and genetic factors are factors that can trigger bruksisme. Therapy of bruksisme include: medicine, selective grinding, orthodontic, stabilization splint,akupunktur and Botox injection. Support care of bruksisme to do, among which psychological treatments, muscle relaxation techniques and biofeedback techniques. There are alternative treatments such as infrared rays therapy.